Polyisocyanurate plastic with rubber-like properties
By using cured polymers with high content of polyether chains and low content of carbamate and isocyanurate groups, combined with fillers and catalysts, polyisocyanurate plastics are prepared by trimerization curing technology, which solves the problems of dimensional instability and permanent compression deformation of existing polyurethane plastics after repeated compression and achieves the effects of high dimensional stability and low compression permanent deformation.
Patent Information
- Application Number
- CN202380055618.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-09
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-07
AI Technical Summary
Existing polyurethane plastics are unstable in size after repeated compression, tend to become brittle, and exhibit high compression permanent deformation at high temperatures, limiting their use in shock absorbers and other applications.
Polyisocyanurate plastics are prepared by trimerization curing technology using cured polymers of high content of polyether chains and low content of carbamate and isocyanurate groups, combined with at least 20% by weight of filler and a catalyst for trimerization of isocyanate groups.
It realizes high dimensional stability, low compression permanent deformation under repeated compression, and maintains good elasticity and mechanical strength at high temperatures, and is suitable for applications that require long-term elasticity.
Smart Images

Figure CN119585332A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to polyisocyanurate plastics and their use as elastomers having rubber-like properties. Prior art
[0002] Natural and synthetic rubbers are obtained by vulcanization, resulting in durable elastomers. Rubber has a low glass transition temperature and good dimensional stability as well as a high elastic recovery after stress. Among other uses, rubber is particularly suitable as elastic seals or damping materials, for example as a component of shock absorbers in vehicle construction. However, over time, rubber tends to become brittle due to oxidation by air and loses its elasticity, which means that the rubber must be replaced regularly. Therefore, there is a need for an elastic plastic with rubber-like properties which does not tend to become brittle when used.
[0003] Polyurethanes are elastic plastics widely used in industry. They have good elasticity and adjustable hardness from soft elasticity to tough elasticity, i.e., low or higher elastic modulus. Polyurethanes are usually cured by the reaction of isocyanate groups with polyols and / or moisture to form urethane bonds and also urea bonds in the case of reaction with moisture. However, the use of polyurethane plastics brings many difficulties. In the case of a one-component system, the water required for curing must penetrate from the outside in the form of atmospheric moisture, and there is always a risk of blistering. This limits the application of such systems in thick layers and between waterproof substrates. The problem with a two-component system comprising a polyol component and an isocyanate component is that the dosage of the components must be very precise in order to achieve an accurate stoichiometric ratio of the curing reaction to provide the desired material properties. In addition, the isocyanate groups can react not only with the hydroxyl groups of the polyols, but also with any water present. Especially at high ambient humidity, this may trigger the formation of bubbles and lead to incomplete polymerization, ultimately resulting in reduced strength and elasticity. Another disadvantage of polyurethane elastomers is that their dimensional stability after compression is significantly lower than that of rubber, which means that they exhibit high compression set and show a significant degree of irreversible plastic deformation when compressed, especially at elevated temperatures. Therefore, polyurethane plastics cannot be used in applications that require long-term dimensional stability after repeated compression and relaxation, such as shock absorbers.
[0004] Plastics are also known which are crosslinked via isocyanurate groups. The isocyanurate groups are formed by trimerization of isocyanate groups. This curing is achieved by adding special alkaline catalysts. Trimerization curing does not require moisture, and the system is quite tolerant of mixing errors when metering the trimerization catalyst. However, the known polyisocyanurate plastics are mostly rigid, high-strength materials with a high glass transition temperature. They are often used as adhesives, resins for composite materials and highly durable varnish-like coatings.
[0005] US2022 / 0145149 describes water-free curing polyisocyanate-based adhesives which cure by trimerization. They have a high content of isocyanate groups, which enables the desired high bond strengths to be achieved.
[0006] EP 2,137,224 describes polyisocyanate-based adhesives suitable for packaging film lamination. These adhesives are cured by reaction of polyisocyanates with substoichiometric amounts of polyols in the presence of trimerization catalysts. A balanced and not too high amount of polyol is required to obtain high adhesion.
[0007] US 5,102,918 describes compositions which are cured by reaction of polyisocyanates with substoichiometric amounts of polyols in the presence of trimerization catalysts, whereby rigid materials are obtained.
[0008] US 3,697,485 describes electron potting compounds obtained by curing a mixture of isocyanate-functional polymers and polyisocyanates by trimerization of isocyanate groups. The cured plastics obtained are not soft enough to exhibit rubber-like properties. SUMMARY OF THE INVENTION
[0010] The object of the present invention is to provide an elastic plastic with rubber-like properties, in particular with high dimensional stability and a compression set comparable to rubber, which overcomes the disadvantages of prior art plastics, in particular with regard to loss of elasticity over time.
[0011] This object is surprisingly achieved with a polyisocyanurate plastic according to claim 1. The plastic according to the invention contains a cured polymer with a very high content of polyether chains and a low content of urethane and isocyanurate groups. It also contains at least 20% by weight of at least one filler and a catalyst for the trimerization of isocyanate groups, wherein the trimerization catalyst is present during the curing reaction and can disappear after curing, for example by evaporation and / or decomposition.
[0012] The polyisocyanurate plastic of the present invention exhibits surprisingly high dimensional stability under repeated compressive stress, which is significantly higher than the corresponding conventional polyurethane plastic that is substantially free of isocyanurate groups. The polyisocyanurate plastic of the present invention exhibits significant rubber-like properties, including very low compression set and does not tend to lose its elasticity over time. It has a very low glass transition temperature, a low elastic modulus and high dimensional stability associated with low compression set, especially after compression at elevated temperatures such as 70°C. The polyisocyanurate plastic is soft and elastic and does not become brittle under cold conditions such as -20°C. It is highly stable to heat and humidity and exhibits good mechanical strength and toughness under good elasticity. The filler contained enables other beneficial properties to be obtained, and therefore, the trimerization cure is surprisingly not negatively affected by the filler. A high content of carbon black filler enables particularly high toughness and excellent dimensional stability to be obtained. A high content of thermally conductive filler enables plastics that are particularly suitable for contact with electronic components or devices, especially batteries of electric vehicles, which generate a lot of heat under heavy loads.
[0013] The polyisocyanurate plastics of the invention are particularly easy to obtain by curing a composition containing a suitable isocyanate-functional polymer with the addition of a trimerization catalyst. There is a high tolerance to mixing errors when a trimerization catalyst is added; and curing does not require water and does not release substances during curing, which enables application in high layer thicknesses and in mostly closed environments, for example for filling gaps or cavities.
[0014] Due to these unique properties, the polyisocyanurate plastics of the invention are perfectly suitable for applications in which an elastic material with soft elasticity and vibration-damping properties and particularly high dimensional stability and low compression set is required. The polyisocyanurate plastics of the invention are particularly suitable as thermally conductive gap fillers for contact with electronic components or devices, in particular batteries of electric vehicles, where the plastic can adapt to the thermal expansion and contraction of the battery components during the charge and discharge cycles, which is known as battery breathing. Also particularly preferred is the use as a vibration-absorbing plastic, in particular for encapsulating steel springs of vehicle shock absorbers.
[0015] Further aspects of the invention are described in the other independent claims. Preferred aspects of the invention are described in the dependent claims. DETAILED DESCRIPTION
[0016] The subject of the present invention is a polyisocyanurate plastic comprising:
[0017] a) a cured polymer, the cured polymer comprising, relative to the total polymer:
[0018] - at least 75% by weight of polyether chains,
[0019] - 1 to 5.2% by weight of urethane groups, and
[0020] - 0.7 to 7% by weight of isocyanurate groups,
[0021] b) at least 20% by weight, relative to the total plastic, of at least one filler.
[0022] As used herein, the term "isocyanurate group" refers to a group of the formula The functional groups can be obtained by trimerization of isocyanate groups.
[0023] As used herein, the term "isocyanate group" refers to a functional group of the following formula: N=C=O.
[0024] As used herein, the term "carbamate group" refers to a group of the formula A functional group which can be obtained by the reaction of an isocyanate group with a hydroxyl group.
[0025] As used herein, a dashed line in a formula represents a bond between a substituent and the relevant residue of the molecule.
[0026] In this document, the content of polyether chains in the cured polymer is calculated from the content of polyether polyols in the cured polymer, all polyether polyols used in the synthesis of the isocyanate-functional polymer to be cured in the polyisocyanurate plastic completely corresponding to the content of polyether chains in the cured polymer with sufficient accuracy. In other words, the mass amount of these polyols corresponds to the mass amount of polyether chains in the cured polymer, thus allowing the calculation of the mass percentage of polyether chains in the cured polymer.
[0027] In this article, the content of carbamate groups in the cured polymer is calculated from the content of hydroxyl groups which react with isocyanate groups to form carbamate groups in the cured polymer, wherein the molar weight of carbamate groups is 59 g / mol (-NH-CO-O-). The molar content of carbamate groups in the cured polymer therefore corresponds exactly to the molar content of hydroxyl groups of the polyol used in the synthesis of the isocyanate-functional polymer to be cured in the polyisocyanurate plastic, from which the mass percentage of carbamate groups in the cured polymer can be calculated.
[0028] In this document, the content of isocyanurate groups in the cured polymer is calculated from the content of isocyanate groups in the uncured polymer before curing, assuming that all isocyanate groups are converted into isocyanurate groups by trimerization. Therefore, the content of isocyanurate groups in the cured polymer (expressed as a percentage by mass relative to the cured polymer) completely corresponds to the content of isocyanate groups in the uncured polymer (expressed as a percentage by mass relative to the uncured polymer).
[0029] The content of isocyanate groups in the uncured polymer is calculated or preferably determined by reaction with a molar excess of dibutylamine and back titration of the remaining dibutylamine with aqueous hydrochloric acid, whereby the molecular weight of the isocyanate groups is 42 g / mol (-NCO).
[0030] As used herein, the term "NCO content" refers to the content of isocyanate groups in % by weight of a molecule, polymer or composition.
[0031] As used herein, a substance name beginning with "poly", such as polyol or polyisocyanate, refers to a substance containing two or more functional groups appearing in its name.
[0032] In this context, the term "plastic" refers to synthetic or semisynthetic materials which are based on crosslinked polymers and are solid at room temperature. The term "polyisocyanurate plastic" refers to plastics based on polymers crosslinked by isocyanurate groups.
[0033] In the present context, the term "filler" refers to a powdery or granular solid material, preferably with a particle size below 2 mm, preferably below 0.5 mm, more preferably below 0.2 mm, in particular below 0.1 mm.
[0034] As used herein, the term "shelf stability" refers to the ability of a composition to be stored in a suitable container at room temperature with the exclusion of moisture for a certain time interval, particularly several months, without experiencing significant changes in application or end-use properties.
[0035] In this context, the term "pot life" refers to the period of time over which a multi-component composition can be applied without defects after the components have been mixed.
[0036] In this context, the term "molecular weight" refers to the molar mass (g / mol) of a molecule. The term "average molecular weight" refers to the number average molecular weight (Mn) of an oligomer or polymer mixture of molecules. It is determined by gel permeation chromatography (GPC) with polystyrene as standard, in particular with tetrahydrofuran as mobile phase and using a refractive index detector.
[0037] Herein, unless otherwise specified, the term "weight %" or "wt %" refers to the mass fraction of a composition component based on the entire composition. The terms "weight" and "mass" are used synonymously herein.
[0038] Herein, "room temperature" refers to a temperature of 23°C.
[0039] If not stated otherwise, all industry standards and specifications mentioned in this document refer to the versions in effect at the time the first application was submitted.
[0040] Preferably, the content of polyether chains is 75 to 97% by weight, in particular 80 to 94% by weight, relative to the total polymer.
[0041] Preferably, the polyether chain consists of repeating units selected from oxyethylene, oxy-1,2-propylene, oxy-1,3-propylene, oxy-1,4-butylene, oxy-1,2-butylene and mixtures thereof, wherein the content of oxyethylene units is less than 20% by weight, preferably less than 10% by weight, in particular less than 5% by weight, based on the total amount of the polyether chain.
[0042] Preference is given to oxyethylene, oxy-1,2-propylene, oxy-1,3-propylene or oxy-1,4-butylene units.
[0043] Particularly preferred are polyether chains consisting of oxy-1,2-propylene units or poly(oxy-1,2-propylene) chains terminated with a certain amount of oxyethylene units. Such materials are readily available and have a high hydrophobicity, which gives polyisocyanurate plastics a high dimensional and hydrolytic stability.
[0044] Preferably, the polyether chain contains no oxyethylene units.
[0045] Most preferably, the polyether chain consists of oxy-1,2-propylene units.
[0046] Preferably, the content of urethane groups is from 1.5 to 4% by weight, in particular from 1.8 to 3.5% by weight, relative to the total polymer.
[0047] Preferably, the content of isocyanurate groups is 1 to 6% by weight, preferably 1.2 to 5% by weight, more preferably 1.4 to 4% by weight and in particular 1.5 to 3% by weight, relative to the total polymer.
[0048] Preferably, the cured polymer contains a portion selected from the group consisting of isomeric diphenylmethane diisocyanate (MDI), isomeric toluene diisocyanate (TDI), naphthalene-1,5-diisocyanate (NDI), 1,5-pentane diisocyanate (PDI), 1,6-hexane diisocyanate (HDI), isophorone diisocyanate (IPDI), isomeric dicyclohexylmethane ... 12 MDI) and mixtures thereof.
[0049] These moieties specifically bond to the urethane and isocyanurate groups of the cured polymer.
[0050] Preference is given to fractions of MDI, IPDI, HDI or mixtures thereof, in particular MDI or IPDI.
[0051] Most preferred is the MDI fraction after removal of the two isocyanate groups.
[0052] MDI is preferably 4,4'-diphenylmethane diisocyanate, which optionally contains a certain amount of 2,4'-diphenylmethane diisocyanate and / or 2,2'-diphenylmethane diisocyanate.
[0053] Preferred cured polymers enable polyisocyanurate plastics to have particularly high thermal and hydrolytic stability, particularly low glass transition temperatures, low elastic moduli at high strength and toughness, and / or particularly high dimensional stability associated with low compression set.
[0054] The polyisocyanurate plastic of the present invention preferably contains 2 to 80% by weight of the cured polymer, relative to the total plastic.
[0055] The polyisocyanurate plastic of the invention further contains at least 20% by weight of at least one filler, preferably 20 to 95% by weight, in particular 30 to 90% by weight, relative to the total plastic. Preferably, the filler content is at least 30% by weight. Such plastics enable high damping properties, in particular with regard to vibrations and / or noise, as well as particularly high dimensional stability and high elastic recovery after compression at elevated temperatures.
[0056] Suitable fillers are, in particular, ground or precipitated calcium carbonate (chalk), optionally surface-coated with fatty acids, for example stearates, barium sulfate (barytes), slate, silicates (quartz), magnesium silicates (talc), aluminum silicates (clays, kaolins), dolomite, mica, glass bubbles, silicic acid, in particular highly dispersed silicic acid from a pyrogenic process (fumed silica), carbon black, graphite, microspheres, pigments, in particular titanium dioxide or iron oxide, calcium oxide, calcium hydroxide, aluminum oxide, aluminum hydroxide, boron nitride, aluminum nitride, magnesium oxide, magnesium hydroxide, zinc oxide, antimony trioxide, antimony pentoxide, boric acid, zinc borate, zinc phosphate, melamine borate, melamine cyanurate, ethylenediamine phosphate, ammonium polyphosphate, bismelamine orthophosphate, bismelamine pyrophosphate, hexabromocyclododecane, decabromodiphenyl ether or tris(bromoneopentyl)phosphate.
[0057] The filler is preferably selected from calcium carbonate, barium sulfate, slate, silicates, magnesium silicates, aluminum silicates, dolomite, mica, fumed silica, carbon black, graphite, titanium dioxide, calcium oxide, calcium hydroxide, aluminum oxide, aluminum hydroxide, boron nitride, aluminum nitride, magnesium oxide, magnesium hydroxide, zinc oxide and any mixtures of these fillers.
[0058] Polyisocyanurate plastics may contain additional ingredients, in particular
[0059] - plasticizers, in particular phthalates, in particular diisononyl phthalate (DINP) or diisodecyl phthalate (DIDP), hydrogenated phthalates, in particular hydrogenated DINP, which is diisononyl 1,2-cyclohexanedicarboxylate (DINCH), terephthalates, in particular bis(2-ethylhexyl) terephthalate (DEHT) or diisononyl terephthalate (DINT), hydrogenated terephthalates, in particular bis(2-ethylhexyl) 1,4-cyclohexanedicarboxylate, trimellitic acid acid esters, adipates, in particular dioctyl adipate (DOA), azelates, sebacates, citrates, benzoates, glycol ethers, glycol esters such as triethylene glycol bis(2-ethylhexanoate), polyether monools or polyether polyols having blocked hydroxyl groups, in particular in the form of acetate groups, organic sulfonates or phosphates, in particular diphenylcresyl phosphate (DPK) or tris(2-ethylhexyl) phosphate (TOP), polybutenes, polyisobutenes or plasticizers obtained from natural fats or oils, such as epoxidized soybean oil or linseed oil,
[0060] - fibres, in particular glass fibres, carbon fibres, metal fibres, ceramic fibres, plastic fibres, in particular polyamide fibres or polyethylene fibres, or natural fibres such as wool, cellulose, hemp or sisal,
[0061] – nanofillers, such as graphene or carbon nanotubes,
[0062] - pigments and / or dyes,
[0063] - Anti-UV or heat stabilizers or antioxidants.
[0064] Preferred plasticizers are glycol esters such as triethylene glycol bis(2-ethylhexanoate), phosphates such as diphenylcresyl phosphate or tris(2-ethylhexyl)phosphate, or customary plasticizers for polyurethanes such as DINP, DIDP, DINCH, DEHT, DINT or DOA.
[0065] In a preferred embodiment of the invention, the amount of filler is at least 50% by weight, preferably at least 60% by weight, more preferably at least 70% by weight, in particular at least 80% by weight, relative to the total plastic, wherein the polyisocyanurate plastic optionally also contains at least one plasticizer. Preferred fillers for such high filler loadings are mineral fillers with an average particle size of more than 1 μm.
[0066] The average particle size of the filler is preferably determined by laser diffraction analysis based on ISO 13320:2009, for example on a CILAS 920 particle size analyzer (Cilas) or on a Malvern Mastersizer 3000 (Malvern).
[0067] Particularly preferred polyisocyanurate plastics with such high filler loadings contain at least one filler selected from graphite, aluminum oxide, aluminum hydroxide, boron nitride, aluminum nitride, magnesium oxide, magnesium hydroxide, zinc oxide and any mixture of these fillers. Among them, aluminum oxide, aluminum hydroxide or magnesium dihydroxide is preferred.
[0068] This polyisocyanurate plastic has a particularly high thermal conductivity. It is particularly suitable for use as a gap filler and / or sealant with high thermal conductivity, which is in contact with electronic components or devices, in particular batteries of electric vehicles. This polyisocyanurate plastic can in particular directly cover, seal or bond batteries, or fill gaps in them. The rubber-like properties together with the good dimensional stability associated with the low compression set make the plastic durable and have vibration damping properties, thereby protecting the battery and enabling heat dissipation, which is generated by the battery during charging or high load. It thus improves the function and life of the battery.
[0069] Particularly preferred polyisocyanate plastics contain, relative to the total plastic:
[0070] - 2 to 10% by weight, preferably 2.5 to 5% by weight, of a cured polymer,
[0071] - 70 to 95% by weight of a filler selected from graphite, aluminum oxide, aluminum hydroxide, boron nitride, aluminum nitride, magnesium oxide, magnesium hydroxide and zinc oxide, and
[0072] - 0 to 30% by weight, preferably 5 to 20% by weight, of plasticizer.
[0073] This plastic has a particularly high thermal conductivity.
[0074] In another preferred embodiment of the invention, the polyisocyanurate plastic contains at least 10% by weight of fillers with an average particle size of less than 1 μm, relative to the total plastic. Such fillers with low particle size have a high surface area and therefore require a large amount of fluid to wet the filler. This means that a small filler loading by weight corresponds to a much higher filler loading by volume. Preferred fillers of such low particle size are carbon black or fumed silica.
[0075] Particularly preferred are polyisocyanurate plastics which contain at least 20% by weight, preferably at least 30% by weight, of carbon black relative to the total plastic. Such plastics are particularly suitable for use as shock-absorbing plastics. They have particularly high strength and toughness and are particularly suitable for encapsulating steel springs for vehicle shock absorbers. They can have durable shock-absorbing properties and high dimensional stability after compression over a wide temperature range.
[0076] Further particularly preferred polyisocyanate plastics contain, relative to the total plastic:
[0077] - 40 to 80% by weight, preferably 50 to 70% by weight, of cured polymer,
[0078] - 20 to 50% by weight, preferably 30 to 50% by weight, of carbon black, and
[0079] - 0 to 40% by weight, preferably 0 to 20% by weight, of plasticizer.
[0080] This polyisocyanate plastic has particularly high shock-absorbing properties.
[0081] The polyisocyanate plastic of the present invention is a solid material with elastic, rubber-like properties. It can be a coating, adhesive, sealant or molding comprising or consisting of the polyisocyanate plastic of the present invention. It is preferably used with high layer thickness.
[0082] Preferably, the layer thickness of the polyisocyanate plastic of the invention is at least 1 mm, preferably at least 2 mm, more preferably at least 4 mm, in particular at least 5 mm, wherein "layer thickness" refers to the smallest dimension related to the length, width and height of the polyisocyanurate plastic.
[0083] This plastic has high dimensional stability associated with low compression set and is able to effectively absorb vibrations and other mechanical deformations.
[0084] The polyisocyanate plastics of the invention have particularly high dimensional stability and low compression set. Preferably, the deformation after compression at 70° C. is less than 50%, preferably less than 40%, in particular less than 30%, the deformation being determined by compressing a cylindrical sample with a diameter of 13 mm and a height of 6 mm at 70° C. by 25% to 4.5 mm in height for 94 hours, subsequently cooling the compressed sample to room temperature, releasing the pressure and measuring the height loss in % based on a compressed height of 1.5 mm.
[0085] The polyisocyanurate plastics of the invention also have a particularly low glass transition temperature. Preferably, the glass transition temperature is below -40°C, in particular below -45°C, determined by DMTA with a stripe sample (width 2.5 mm, length 8.5 mm, thickness 2 mm), measured in shear mode at an excitation frequency of 1 Hz and a heating rate of 5 K / min, wherein the glass transition temperature corresponds to the temperature at the maximum of the loss modulus.
[0086] Another subject of the present invention is a process for obtaining the polyisocyanurate plastic according to the invention, comprising the following steps:
[0087] i) providing a composition comprising
[0088] at least one isocyanate-functional polymer containing at least 75% by weight of polyether chains, 1 to 5.2% by weight of urethane groups and 0.7 to 4% by weight of isocyanate groups, relative to the total polymer,
[0089] - and at least 20% by weight, relative to the total composition, of at least one filler,
[0090] ii) adding at least one catalyst for trimerization of isocyanate groups, and
[0091] iii) curing the composition by trimerization of the isocyanate groups, preferably at a temperature of 5 to 100°C, more preferably 10 to 90°C, in particular 15 to 80°C.
[0092] The composition provided in step i) contains at least one isocyanate-functional polymer having at least 75% by weight of polyether chains, 1 to 5.2% by weight of urethane groups and 0.7 to 4% by weight of isocyanate groups.
[0093] The isocyanate-functional polymer is preferably liquid at room temperature. It preferably has a low viscosity, preferably 1-200 Pa·s, preferably 1-100 Pa·s, more preferably 2-50 Pa·s, in particular 3-25 Pa·s, which is measured at 20° C. using a cone-plate rheometer with a cone diameter of 25 mm, a cone angle of 1°, and a cone-plate distance of 0.05 mm for 10 s. -1 Measured at a shear rate of .
[0094] The content and nature of the polyether chains of the isocyanate-functional polymer preferably correspond to those described and preferred for the cured polymer contained in the polyisocyanurate plastics according to the invention.
[0095] The content and nature of the urethane groups of the isocyanate-functional polymer preferably correspond to the content and nature described and preferred for the cured polymer contained in the polyisocyanurate plastic of the invention.
[0096] The isocyanate-functional polymer preferably has a content of isocyanate groups of 1 to 3.5% by weight, in particular 1.5 to 3% by weight, relative to the total polymer.
[0097] The average molecular weight M of the isocyanate functional polymer n It is preferably 2000 g / mol to 15000 g / mol, particularly 3000 g / mol to 10000 g / mol.
[0098] The isocyanate-functional polymers are preferably obtained from the reaction of at least one monomeric diisocyanate and at least one polyether polyol.
[0099] Suitable monomeric diisocyanates are, in particular, 4,4′-diphenylmethane diisocyanate, 2,4′-diphenylmethane diisocyanate, 2,2′-diphenylmethane diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, naphthalene-1,5-diisocyanate, 3,3′-dimethyl-4,4′-diisocyanatobiphenyl, 1,4-butane diisocyanate, 1,5-pentane diisocyanate, 2-methyl-1,5-pentane diisocyanate, 1,6-hexane diisocyanate, 2,2(4),4-trimethyl-1,6-hexane diisocyanate, esters, 1,10-decane diisocyanate, 1,12-dodecane diisocyanate, cyclohexane-1,3-diisocyanate, cyclohexane-1,4-diisocyanate, 1-methyl-2,4-diisocyanatocyclohexane, 1-methyl-2,6-diisocyanatocyclohexane, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, 1,4-bis(isocyanatomethyl)cyclohexane, m-xylylene diisocyanate, p-xylylene diisocyanate or 3,6-bis-(9-isocyanatononyl)-4,5-di(1-heptenyl)cyclohexene (dimeric diisocyanate).
[0100] Preferred among them are isomeric diphenylmethane diisocyanate (MDI), isomeric toluene diisocyanate (TDI), naphthalene-1,5-diisocyanate (NDI), 1,5-pentane diisocyanate (PDI), 1,6-hexane diisocyanate (HDI), isophorone diisocyanate (IPDI) or isomeric dicyclohexylmethane diisocyanate (HDI). 12 MDI) and mixtures thereof, preferably MDI, HDI or IPDI, in particular MDI or IPDI.
[0101] Most preferred is MDI, preferably 4,4'-diphenylmethane diisocyanate, which optionally contains some 2,4'-diphenylmethane diisocyanate and / or 2,2'-diphenylmethane diisocyanate.
[0102] Suitable polyether polyols are in particular polyether polyols having repeating units selected from the group consisting of oxyethylene, oxy-1,2-propylene, oxy-1,3-propylene, oxy-1,4-butylene, oxy-1,2-butylene and mixtures thereof, wherein the content of oxyethylene units is less than 20% by weight, preferably less than 10% by weight and in particular less than 5% by weight, based on the total polyol.
[0103] Particularly preferred are poly(oxy-1,2-propylene)diols or trimethylolpropane or glycerol-started poly(oxy-1,2-propylene)triols, which are optionally terminated with some ethylene oxide. Preferred are poly(oxy-1,2-propylene)diols or triols that do not contain oxyethylene units. Particularly preferred are poly(oxy-1,2-propylene)diols.
[0104] Preferably, the OH value of the polyether polyol is in the range of 10 to 60 mg KOH / g.
[0105] Preferred are polyether polyols having an unsaturation of less than 0.02 meq / g, preferably less than 0.01 meq / g.
[0106] Particularly preferred is the average molecular weight M n A polyether diol having an average molecular weight M of 1800-12000 g / mol, preferably 2000-8,000 g / mol n The polyether triol is 3000-10000 g / mol, preferably 4000-8000 g / mol. The most preferred is polyether diol.
[0107] The isocyanate-functional polymer is preferably prepared by combining at least one monomeric diisocyanate and at least one polyether polyol in an NCO / OH molar ratio of at least 1.3, preferably at least 1.5, more preferably at least 1.8, in the absence of moisture, at a temperature of 20 to 160° C., preferably 40 to 140° C., optionally in the presence of a suitable catalyst.
[0108] Particularly preferred isocyanate functional polymers have a monomeric diisocyanate content of less than 0.5 wt. %, preferably less than 0.3 wt. %, more preferably less than 0.2 wt. %, most preferably less than 0.1 wt. %, relative to the total polymer. Such low monomer content isocyanate functional polymers allow for curable compositions having a monomeric diisocyanate content of less than 0.1 wt. % and are safe to use without special protective measures and do not require hazard marking.
[0109] For such polymers, the reaction is preferably carried out at an NCO / OH molar ratio of at least 3 / 1, preferably 3 / 1 to 10 / 1, in particular 3 / 1 to 8 / 1, and the majority of the remaining monomeric diisocyanate is then removed by distillation, preferably by thin-film distillation or short-path distillation under vacuum.
[0110] Another possibility for obtaining isocyanate-functional polymers having a low monomeric diisocyanate content is by chemically reducing the monomeric diisocyanate content, for example by adding small amounts of water, preferably in combination with surfactants.
[0111] The composition provided in step i) further contains at least 20% by weight of at least one filler, wherein the nature of the filler preferably corresponds to the fillers described and preferred for the polyisocyanurate plastics of the present invention. The amount of filler in the composition provided in step i) can be lower than in the polyisocyanurate plastics of the present invention, since some additional filler can be added in step ii) together with the catalyst.
[0112] In addition to the already mentioned further ingredients which are optionally contained in the polyisocyanurate plastic of the invention, the composition of step i) may preferably further contain small amounts of
[0113] - oligomeric polyisocyanates, such as biuret or isocyanurate or uretdione or iminooxadiazinedione or allophanate of HDI, isocyanurate of IPDI, isocyanurate of PDI or mixed isocyanurate based on TDI and HDI, preferably isocyanurate of HDI,
[0114] – Desiccants, especially molecular sieves, calcium oxide, highly reactive isocyanates such as p-toluene isocyanate, monooxazolidines such as 2 (from Incorez) or orthoformates, of which calcium oxide is particularly preferred,
[0115] - adhesion promoters, in particular organoalkoxysilanes, for example 3-isocyanatopropyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, (meth)acryloylsilane, anhydridesilane, carbamatesilane, alkylsilane or iminosilane, or oligomers thereof, or titanates,
[0116] - thickeners, such as bentonites, castor oil derivatives, hydrogenated castor oil, polyamides, polyamide waxes, polyurethanes, urea compounds, pyrogenic silicas, cellulose ethers or hydrophobically modified polyoxyethylenes,
[0117] - organic solvents,
[0118] - Additives, such as wetting agents, flow enhancers, leveling agents, defoamers, deaerators or biocides.
[0119] Preferably, the composition contains at least one desiccant, in particular calcium oxide. Calcium oxide reacts with water to form calcium hydroxide, thereby preventing water that may be contained in the filler from reacting with isocyanate groups when the composition is stored.
[0120] The composition provided in step i) is prepared by mixing all ingredients under the exclusion of water to obtain a macroscopically homogeneous fluid or paste and storing in a moisture-proof container at ambient temperature. Suitable moisture-proof containers are preferably buckets, barrels, pails, bags, sleeves, boxes, cans, bottles or tubes. Under suitable packaging and storage, the composition shows good shelf stability.
[0121] In step ii), at least one catalyst for the trimerization of isocyanate groups is added to the composition.
[0122] Suitable trimerization catalysts are generally basic substances which catalyze the trimerization of isocyanate groups at room temperature.
[0123] Suitable catalysts are in particular tertiary amines, for example triethylamine, tributylamine, N,N-dimethylpiperazine or 1,4-diazabicyclo[2.2.2]octane (DABCO), or hydroxylamines, for example triethanolamine or dimethylethanolamine. Other suitable catalysts are in particular amidines, for example 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), or guanidines, for example 1,1,3,3-tetramethylguanidine or 1-hexyl-2,3-diisopropylguanidine. Other suitable catalysts are in particular phenols containing tertiary amine groups, for example 2,4,6-tris(dimethylaminomethyl)phenol or disodium 2,6-bis(N-methyl-N-carboxymethyl-aminomethyl)-4-nonylphenol. Other suitable catalysts are in particular tetraalkylammonium hydroxides, for example tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide or trimethylhydroxypropylammonium hydroxide. Other suitable catalysts are in particular ammonium salts of carboxylic acids, for example trimethylhydroxypropylammonium formate, trimethylammonium pivalate or tetraethylammonium acetate. Other suitable catalysts are in particular metal salts of carboxylic acids, for example potassium acetate, potassium 2-ethylhexanoate, potassium neodecanoate, stannous octoate or sodium benzoate. Other suitable catalysts are in particular alkali metal phenolates, for example sodium phenolate or potassium phenolate, or alkali metal alcoholates. Other suitable catalysts are in particular metal complexes of crown ethers, ethers or carboxylates, for example zirconium tetra-n-butyrate or zirconium tetra-2-ethylhexanoate. Other suitable catalysts are in particular phosphorus-containing substances, for example trioctylphosphine or tetrabutylphosphonium fluoride.
[0124] Particularly preferred trimerization catalysts are tetraethylammonium hydroxide, trimethyl-2-hydroxypropylammonium formate, trimethylammonium pivalate, potassium 2-ethylhexanoate, potassium neodecanoate, disodium 2,6-bis(N-methyl-N-carboxymethyl-aminomethyl)-4-nonylphenol or stannous octoate.
[0125] Catalysts which are solid at room temperature are preferably used as solutions in suitable liquids, preferably diols or diethylene glycol and / or plasticizers.
[0126] Suitable trimerization catalysts are commercially available, in particular as TMR-2 TMR-7, TMR-12 or TMR-31 (both from Evonik).
[0127] The amount of the trimerization catalyst added is preferably 0.01 to 5% by weight, more preferably 0.02 to 3% by weight, and in particular 0.05 to 1% by weight, relative to the total polyisocyanurate plastic obtained.
[0128] The catalyst can be added in pure form or as a concentrated solution containing 20-80% by weight of the catalyst. However, since the amount of catalyst relative to the composition provided in step i) is very low, it is preferred to add the catalyst in highly diluted form so that the mixing ratio by weight between the composition and the diluted catalyst is 10:1 to 1:1. Such highly diluted catalyst preferably contains a plasticizer and optionally a filler.
[0129] In a preferred embodiment of the process, the composition in step i) is referred to as the "isocyanate component" and the catalyst added in step ii) is added in diluted form as the so-called "catalyst component".
[0130] Preferred catalyst components contain a plasticizer and optionally a filler, wherein preferably the same filler and plasticizer are part of the isocyanate component.
[0131] Preferably, the isocyanate component and the catalyst component are packaged separately and stored separately in moisture-proof containers having good shelf-life stability before they are mixed with one another in step ii) of the process.
[0132] The catalyst in step ii) can be added by any possible mixing procedure.
[0133] Preferably, the addition of the catalyst in step ii) is performed by a static or dynamic mixing step. Preferably, the catalyst is added in diluted form, in particular as part of a catalyst component further comprising a plasticizer and optionally a filler.
[0134] Step ii) is preferably carried out at ambient temperature, preferably at 5 to 40°C, more preferably 10 to 35°C, in particular 15 to 30°C.
[0135] On mixing, the trimerization catalyst comes into contact with the isocyanate functional polymer, whereby curing begins by trimerization of the isocyanate groups in step iii).
[0136] Curing in step iii) can be carried out at ambient temperature or at elevated temperature, preferably at a temperature of 5 to 100 °C, more preferably 10 to 90 °C, in particular 15 to 80 °C.
[0137] During the curing step iii), the composition with the admixed catalyst is preferably in contact with one or more than one substrate, preferably a moisture-proof substrate, which covers substantially the entire surface of the mixed material. This means that the surface of the mixed material is preferably not exposed or only minimally exposed to moisture from the air during curing.
[0138] During curing, some side reactions may also occur, such as the reaction of isocyanate groups with water to form urea groups, thereby releasing carbon dioxide, or forming a urea having the formula An asymmetric trimer of a functional group, called the iminooxadiazinedione group.
[0139] The use of a suitable catalyst in a suitable amount and a hydrophobic isocyanate-functional polymer having a low content of ethylene oxide or no ethylene oxide units in the polyether chain ensures that predominantly isocyanurate groups are formed upon curing. Preferably, at least 90% of the isocyanate groups present in the composition of step i) are converted into isocyanurate groups upon curing.
[0140] Another subject of the invention is the use of the polyisocyanurate plastic as a gap filler, in particular as a gap filler with high thermal conductivity, or as a shock absorber, as a vibration or noise damping material, as a coating, as an adhesive or as a sealing material. For these uses, the elasticity, rubber-like properties and high dimensional stability and low compression set of the polyisocyanurate plastic according to the invention, combined with simple application, high tolerance to mixing errors, no need for moisture curing and no release of substances such as carbon dioxide, ethanol or methanol during curing, are of great advantage.
[0141] For these uses, the mixed composition from step ii) of the process is preferably brought to the desired location and shaped as it is intended to cure while it is still processable, meaning within the pot life of the mixed composition. This process is called application.
[0142] The mixed composition is preferably applied by injecting it into a mold or - in the case of a gap filler - into a space or gap, or - in the case of a coating, sealant or adhesive - by placing it on a substrate or between two or more substrates.
[0143] Particularly preferred application is effected from a cartridge, preferably from a twin cartridge via a static mixer, or from a combined mixing and pumping device with an integrated static or dynamic mixer.
[0144] Another particularly preferred application is by simply pouring the mixed composition into a mold or gap and allowing it to fill the space to the desired extent.
[0145] Particularly preferred uses are as gap fillers and / or sealants with high thermal conductivity, which are in contact with electronic components or devices, in particular batteries of electric vehicles. Such polyisocyanurate plastics can directly cover, seal or bond batteries, or fill gaps within them. The rubber-like properties and high dimensional stability associated with low compression set give the plastics a durable function of vibration-damping properties, thereby protecting the battery and enabling heat dissipation, which is generated during charging or heavy loads. It thereby improves the functionality and life of the battery.
[0146] In this regard, another preferred use of some embodiments of the plastic according to the invention is as an elastic adhesive, especially in battery box bonding, for example for bonding battery box covers. In this use, the unique properties of the polyisocyanurate plastic according to the invention, including elastic recovery and thermal and oxidative stability, bring useful technical advantages.
[0147] Another particularly preferred use is as a shock-absorbing plastic, in particular for encapsulating steel springs for vehicle shock absorbers. It enables long-lasting shock-absorbing properties and high dimensional stability, high elastic recovery after compression over a wide temperature range, and does not become brittle due to oxidation in air.
[0148] BRIEF DESCRIPTION OF THE DRAWINGS
[0149] Figure 1 Shown are the storage modulus and loss modulus versus temperature plots for Example 2, determined using the DMTA measurements as described.
[0150] Example
[0151] The following examples illustrate the invention without limiting it.
[0152] “Standard climatic conditions” means a temperature of 23±1° C. and a relative atmospheric humidity of 50±5%, and is abbreviated as “SCC”.
[0153] Chemicals not otherwise specified were from Sigma-Aldrich Chemie GmbH and used as received.
[0154] Preparation of isocyanate functional polymers
[0155] The NCO content is determined by reaction with a molar excess of dibutylamine and back titration of the remaining dibutylamine with aqueous hydrochloric acid.
[0156] The viscometer was Rheotec RC30 (cone diameter 50 mm, cone angle 1°, cone-plate distance 0.05 mm, shear rate 10 s -1 ) to measure viscosity.
[0157] The monomeric diisocyanate content was determined by HPLC (detection by photodiode array, 0.04 M sodium acetate / acetonitrile mobile phase) after derivatization with N-propyl-4-nitrobenzylamine.
[0158] Substances used
[0159] 5031 BT Ethylene oxide terminated polyoxypropylene triol, OH value 28 mg KOH / g (from Covestro)
[0160] 4200 Polyoxypropylene glycol, OH value 28mg KOH / g (from Covestro)
[0161] CP 4755 Ethylene oxide terminated polyoxypropylene triol, OH value 35.0 mg KOH / g (from Dow)
[0162] 1010L Polyoxypropylene glycol, OH value 112 mg KOH / g (from Dow)
[0163] MDI 4,4'-diphenylmethane diisocyanate ( 44MC L, from Covestro)
[0164] IPDI Isophorone diisocyanate ( IPDI, from Evonik)
[0165] Polymer P1
[0166] 725.0g 5031BT and 275 g of MDI were reacted according to known procedures at 80° C. to form a mixture with an NCO content of 7.6% by weight. The volatile content, in particular most of the monomeric MDI, was then removed from the mixture by distillation in a short-path evaporator (jacket temperature 180° C., 0.1-0.005 mbar), thereby obtaining a polymer with an NCO content of 1.7% by weight, a viscosity of 19 Pa·s at 20° C. and a monomeric MDI content of 0.04% by weight.
[0167] Polymer P2
[0168] 1300g 4200、2600g CP 4755, 600 g of MDI and 500 g of diisodecyl phthalate (plasticizer) were reacted at 80° C. according to known procedures, thereby obtaining a polymer having an NCO content of 2.1% by weight, a viscosity of 57 Pa·s at 20° C. and a monomeric MDI content of about 2.2% by weight.
[0169] Polymer P3
[0170] 727g 4200 and 273 g of MDI were reacted according to known procedures at 80° C. to form a mixture with an NCO content of 7.6% by weight. The volatile content, in particular most of the monomeric MDI, was then removed from the mixture by distillation in a short-path evaporator (jacket temperature 180° C., 0.1-0.005 mbar), thereby obtaining a polymer with an NCO content of 1.7% by weight, a viscosity of 15 Pa·s at 20° C. and a monomeric MDI content of 0.08% by weight.
[0171] Polymer P4
[0172] 400g 4200 and 52 g of MDI were reacted at 80° C. according to known procedures, thereby obtaining a polymer having an NCO content of 1.8% by weight, a viscosity of 32 Pa·s at 20° C. and a monomeric MDI content of about 2.3% by weight.
[0173] Polymer P5
[0174] 780g 5031BT and 303 g of IPDI were reacted according to known procedures at 80° C. to form a mixture with an NCO content of 9.1% by weight. The volatile content, in particular most of the monomeric IPDI, was then removed from the mixture by distillation in a short-path evaporator (jacket temperature 160° C., 0.1-0.005 mbar), thereby obtaining a polymer with an NCO content of 1.8% by weight, a viscosity of 8.2 Pa·s at 20° C. and a monomeric IPDI content of 0.02% by weight.
[0175] Polymer P6
[0176] 590g 4200、1180g CP 4755 and 230 g of IPDI were reacted at 80° C. according to known procedures, thereby obtaining a polymer having an NCO content of 2.1% by weight, a viscosity of 22 Pa·s at 20° C. and a monomeric IPDI content of about 1.8% by weight.
[0177] Polymer P7
[0178] 600g 1010 L and 533.3 g of IPDI were reacted at 80° C. according to known procedures to form a mixture with an NCO content of 15.6 wt.-%. The volatile content, in particular most of the monomeric IPDI, was then removed from the mixture by distillation in a short-path evaporator (jacket temperature 160° C., 0.1-0.005 mbar), thereby obtaining a polymer with an NCO content of 5.2 wt.-%, a viscosity of 21.8 Pa·s at 20° C. and a monomeric IPDI content of 0.03 wt.-%.
[0179]
[0180]
[0181] Table 1: Overview of the isocyanate-functional polymers used.
[0182] 1 Relative to total polymer without plasticizer
[0183] 2 Calculated from the content of polyether polyol
[0184] 3 Calculated from the content of hydroxyl groups that react with isocyanate groups
[0185] Preparation of curable polymers crosslinked with isocyanurate groups
[0186] Catalyst used
[0187] TMR-2 contains trimethyl-2-hydroxypropyl ammonium formate TMR-2 (from Evonik)
[0188] TMR-7 contains trimethylammonium pivalate TMR-7 (from Evonik)
[0189] TMR-12 contains potassium 2-ethylhexanoate and trimethylammonium pivalate. TMR-12 (from
[0190] Evonik
[0191] TMR-31 contains disodium 2,6-bis(N-methyl-N-carboxymethyl-aminomethyl)-4-nonylphenol
[0192] TMR-31 (from Evonik)
[0193] TOP trioctylphosphine 97% (from Sigma Aldrich)
[0194] Compositions C-1 to C-10
[0195] For each composition, 100 parts by weight of the isocyanate functional polymer as given in Table 2-4 and the catalyst as given in Table 2-4 in the given amount (parts by weight) were mixed by a centrifugal mixer (SpeedMixer TM DAC 150, FlackTek Inc.) was mixed under vacuum and moisture exclusion, and the mixed composition was subsequently applied to the tests given below. For composition C-5 (Ref.), the isocyanate functional polymer and HDI-isocyanurate were mixed in advance in a given amount using a centrifugal mixer, and then the catalyst was added as described.
[0196] In order to measure mechanical properties, the composition is poured into a PTFE-coated mold to obtain a film with a layer thickness of about 2 mm, which is immediately covered with a PTFE-coated metal plate and stored for 7 days under a standard climate. The film is then taken out of the mold and a dumbbell-shaped sample is punched out from a cured film of 75 mm in length with a bridge length of 30 mm and a bridge width of 4 mm. The sample prepared in this way is used to measure tensile strength, elongation (at break) and E-modulus 5% (elastic modulus from 0.5 to 5% elongation) at a crosshead speed of 200 mm / min according to DIN EN 53504. These results are marked with "covered curing (RT)". For some compositions, identical films are prepared, which are not covered with a PTFE-coated metal plate, but are cured for 7 days with an open surface under a standard climate. These results are marked with "open curing (SCC)".
[0197] The Tg value (glass transition temperature) was determined by DMTA measurement as described in Example 1.
[0198] The cured films of all these examples were transparent, uniform and free of bubbles.
[0199] The test results are given in Tables 2 to 4.
[0200] Reference compositions are marked with "(Ref.)".
[0201]
[0202] Table 2: Composition and properties of compositions C-1 to C-5.
[0203] “nd” means “not determined”
[0204] 1 NCO content 23% by weight ( N 3600, from Covestro)
[0205] 2 Calculated from isocyanate content
[0206] 3 Based on total polymer (without plasticizer)
[0207]
[0208] Table 3: Compositions and properties of compositions C-6 to C-8.
[0209] “nd” means “not determined”
[0210] 1 Calculated from isocyanate content
[0211]
[0212] Table 4: Composition and properties of compositions C-9 and C-10.
[0213] Composition of Table 5
[0214] For each composition, 10 g of an isocyanate functional polymer as given in Table 5 was mixed with a catalyst as given in Table 5 in a given amount (wt % relative to the total polymer) by a centrifugal mixer under vacuum and exclusion of moisture, and then the tack-free time (TFT) was measured.
[0215] To determine the TFT opening (SCC), the freshly mixed material was applied to cardboard in a layer thickness of about 5 mm under standard climate and the surface was then lightly touched from time to time with an LDPE pipette until the contact did not leave any polymer residues on the pipette.
[0216] The test results are given in Table 5.
[0217]
[0218] Table 5: Tack-free time (TFT) of different polymers with various contents of trimerization catalyst
[0219] Examples 1 and 2 (suitable for use as shock-absorbing plastics)
[0220] For each composition, the isocyanate component was prepared by mixing the ingredients as given in Table 6 in the given amounts (parts by weight) by means of a planetary mixer under vacuum and exclusion of moisture and stored in a moisture-proof container.
[0221] When used, the catalyst components given in Table 6 were added to the isocyanate component in a given amount (parts by weight) and mixed by a centrifugal mixer (SpeedMixer) under the condition of excluding moisture. TM DAC 150, FlackTek Inc.) and then the mixed composition was applied for the tests given below.
[0222] The viscosity was measured at 25° C. after mixing for 60 seconds with a rheometer MCR 101 from Anton Paar in a rotational test with plates PP25, gap width 0.2 mm and speed 2 rpm.
[0223] In order to measure mechanical properties, the composition is applied between two PTFE-coated foils, and is pressed into a film of about 2mm in thickness with two metal plates. The film covered with two metal plates is then cured in an oven at 60 ℃ for 1 hour, then at 80 ℃ for 23 hours. The metal plate and the PTFE-coated foil are then taken out from the cured film. The film is then stored under standard climate for 24 hours, and then from the cured film, a dumbbell-shaped sample with a length of 75mm, a bridge length of 30mm and a bridge width of 4mm is punched out. For the sample prepared in this way, tensile strength, elongation (when broken) and E-modulus 5% (elastic modulus from 0.5% to 5% elongation) are measured at a crosshead speed of 200mm / min according to DIN EN 53504. Punch out additional test specimens from the cured film to measure tear propagation and according to DIN ISO 34-1, method B (angle specimen) is measured at a crosshead speed of 500mm / min. These results are marked as "Cure 1h 60°C / 23h 80°C".
[0224] As a measure of thermal stability, additional dumbbell-shaped samples were stored in an oven at 100°C for 7 days and then stored in a standard climate for 24 hours. These samples were then tested for tensile strength, elongation and 5% E-modulus as described above. These results are marked with "after 7 days storage at 100°C".
[0225] The Shore A hardness is determined according to DIN 53505 with cylindrical specimens of 20 mm diameter and 5 mm thickness which have been cured in an oven at 60° C. for 1 hour with a PTFE-coated metal plate covered therewith and then at 80° C. for 23 hours and then stored in a standard climate for 24 hours.
[0226] Using the Rheoplus MCR 302 instrument from Anton Paar, DMTA measurements were performed on strip samples (2.5 mm wide, 8.5 mm long, 2 mm thick) cut from the prepared cured film to determine the mechanical properties. The measurement conditions were: measurement in shear mode, an excitation frequency of 1 Hz, and a heating rate of 5 K / min. The sample was cooled to -100°C and heated to 200°C, and the storage modulus and loss modulus were determined, whereby the temperature at the maximum value of the loss modulus was read as the Tg value (glass transition temperature).
[0227] exist Figure 1 In FIG. 1 , the storage modulus and loss modulus curves of Example 15 with respect to temperature are given.
[0228] The dimensional stability after compression at 70 ℃ is determined based on DIN ISO 815-1 (determination of compression set). For this test, several test samples are prepared by applying the composition to a cylindrical mold with a diameter of 13mm and a height of 6mm. Cover the surface with a metal cover and cure the sample in an oven at 60 ℃ for 1 hour, then cure at 80 ℃ for 23 hours, remove from the mold and store for 24 hours under standard climate. Then measure the exact height (thickness) of each cylindrical sample, and then compress the sample by 25% of the height (i.e., compressed to 75% of the initial height) by a press with two metal plates held together by 4 screws. Then the compressed sample is stored in an oven at 70 ℃ for 94 hours. After the sample is cooled to room temperature, the compression is released, which allows the cylindrical sample to recover. After waiting for 30 minutes under standard conditions, the recovered height is measured, and the deformation (in %) is calculated by dividing the height loss (i.e., the initial height minus the recovered height) by the compressed height (i.e., 25% of the initial height).
[0229] In order to compare the dimensional stability after compression, 803L45 (from Sika), a commercial two-component polyurethane adhesive filled with carbon black having a Shore A hardness of 82, a tensile strength of 10 MPa, an elongation at break of 300% and a Tg of -40°C, was also cured in the form of cylindrical specimens having a diameter of 13 mm and a height of 6 mm, stored under standard conditions for 7 days, then stored in an oven at 60°C for 24 hours and again under standard conditions for 24 hours, and these specimens were then tested in the same manner as described.
[0230] The results are given in Tables 6 and 7.
[0231] have Reference examples of 803L45 are marked with "(Ref.)".
[0232]
[0233] Table 6: Composition and properties of Examples 1 and 2
[0234] "nd" means "not determined"
[0235] 120 (from Cabot)
[0236]
[0237] Table 7: Dimensional stability of Examples 1 and 2 after compression at 70°C compared to commercial polyurethane materials.
[0238] Example 3
[0239] 100 parts by weight of the isocyanate component of Example 2 were mixed with several amounts of catalyst TMR-2 (in parts by weight) given in Table 8 by means of a centrifugal mixer. For each mixed composition, the pot life was determined by viscosity measurement (viscosity measurement as described in Example 2), whereby the bottom plate of the rheometer was heated to the temperature given in Table 8. The measurement was continued until the viscosity at a given temperature reached or exceeded 500 Pa·s (=end of pot life).
[0240]
[0241] Table 8: Pot life of Example 3 at different catalyst concentrations and temperatures.
[0242] Examples 4 and 5 (suitable for use as thermally conductive gap fillers)
[0243] For each composition, the mixture was mixed by centrifugal mixer (SpeedMixer TM The isocyanate component was prepared by mixing the ingredients given in Table 9 in the given amounts (parts by weight) while excluding moisture and storing in a moisture-proof container.
[0244] The catalyst component was prepared in the same manner by mixing the ingredients given in Table 9 and stored in a moisture proof container.
[0245] When used, the isocyanate component and the catalyst component were mixed by a centrifugal mixer to obtain a homogeneous paste which was immediately tested as follows:
[0246] The Shore A hardness is determined in accordance with DIN 53505 using cylindrical specimens with a diameter of 20 mm and a thickness of 6 mm which have been cured for 7 days in a standard climate with a PTFE-coated foil and a metal cover.
[0247] Appearance was determined visually on samples prepared for Shore A measurements by judging the surfaces and cutting them to expose the internal material.
[0248] Thermal conductivity was determined according to ASTM D5470-12 on samples cured for 7 days under standard climatic conditions. For the test, a TIM (Thermal Interface Material) test device (obtained from Zentrum für Stuttgart, Germany) was used. ) was measured using the fixed cylinder method. The sample dimensions were: 30 mm diameter, 2 mm and 6 mm thickness. The pressure parameters measured were 1, 2, 3, 5, 7, and 10 bar.
[0249] The results are given in Table 9.
[0250]
[0251] Table 9: Composition and properties of Examples 4 and 5.
[0252] 1 Triethylene glycol bis(2-ethylhexanoate), plasticizer (from Eastman)
[0253] 2 Surface treated aluminum hydroxide ( TM-3810 from Huber Martinswerk), dried at 130° C. for 10 hours.
Claims
1. Polyisocyanurate plastics, which contain a) a cured polymer, the cured polymer comprising, relative to the total polymer: - at least 75% by weight of polyether chains, - 1 to 5.2% by weight of urethane groups, and - 0.7 to 7% by weight of isocyanurate groups, b) at least 20% by weight, relative to the total plastic, of at least one filler.
2. The polyisocyanurate plastic according to claim 1, wherein the content of polyether chains is 75 to 97% by weight, preferably 80 to 94% by weight, relative to the total polymer.
3. The polyisocyanurate plastic according to claim 1 or 2, wherein the polyether chain consists of repeating units selected from the group consisting of oxyethylene, oxy-1,2-propylene, oxy-1,3-propylene, oxy-1,4-butylene, oxy-1,2-butylene and mixtures thereof, wherein the content of oxyethylene units is less than 20% by weight, preferably less than 10% by weight, in particular less than 5% by weight, based on the total amount of the polyether chain.
4. The polyisocyanurate plastic according to any one of claims 1 to 3, wherein the content of isocyanurate groups is 1 to 6% by weight, preferably 1.2 to 5% by weight, more preferably 1.4 to 4% by weight, in particular 1.5 to 3% by weight, relative to the total polymer.
5. The polyisocyanurate plastic according to any one of claims 1 to 4, wherein the cured polymer contains a portion selected from the group consisting of isomeric diphenylmethane diisocyanates, isomeric toluene diisocyanates, naphthalene-1,5-diisocyanates, 1,5-pentane diisocyanates, 1,6-hexane diisocyanates, isophorone diisocyanates, isomeric dicyclohexylmethane diisocyanates and mixtures thereof after removal of two isocyanate groups.
6. The polyisocyanurate plastic according to any one of claims 1 to 5, wherein the at least one filler is selected from the group consisting of calcium carbonate, barium sulfate, slate, silicates, magnesium silicates, aluminum silicates, dolomite, mica, fumed silica, carbon black, graphite, titanium dioxide, calcium oxide, calcium hydroxide, aluminum oxide, aluminum hydroxide, boron nitride, aluminum nitride, magnesium oxide, magnesium hydroxide, zinc oxide, and any mixture of these fillers.
7. The polyisocyanurate plastic according to any one of claims 1 to 6, wherein the amount of filler is at least 50% by weight, preferably at least 60% by weight, more preferably at least 70% by weight, in particular at least 80% by weight, relative to the total plastic, wherein the polyisocyanurate plastic optionally further contains at least one plasticizer.
8. The polyisocyanurate plastic according to claim 7, wherein the polyisocyanurate plastic contains at least one filler selected from the group consisting of graphite, aluminum oxide, aluminum hydroxide, boron nitride, aluminum nitride, magnesium oxide, magnesium hydroxide, zinc oxide, and any mixture of these fillers.
9. The polyisocyanurate plastic according to any one of claims 1 to 8, which contains, relative to the total plastic: – 2 to 10% by weight of cured polymer, - 70 to 95% by weight of a filler selected from graphite, aluminum oxide, aluminum hydroxide, boron nitride, aluminum nitride, magnesium oxide, magnesium hydroxide and zinc oxide, and - 0 to 30% by weight of plasticizer.
10. The polyisocyanurate plastic according to claim 1 , wherein the polyisocyanurate plastic contains at least 10% by weight of fillers with an average particle size of less than 1 μm, preferably carbon black or fumed silica, relative to the total plastic, in particular at least 20% by weight, preferably at least 30% by weight of carbon black, wherein the average particle size is determined by laser diffraction analysis based on ISO 13320:2009, for example on a CILAS 920 particle size analyzer or on a Malvern Mastersizer 3000.
11. The polyisocyanurate plastic according to claim 10, comprising, relative to the total plastic: – 40 to 80% by weight of cured polymer, - 20 to 50% by weight of carbon black, and - 0 to 40% by weight of plasticizer.
12. The polyisocyanurate plastic according to any one of claims 1 to 11, wherein the deformation of the polyisocyanurate plastic after compression at 70°C is less than 50%, preferably less than 40%, and in particular less than 30%, the deformation being determined by compressing a cylindrical sample with a diameter of 13 mm and a height of 6 mm at 70°C by 25% to 4.5 mm in height for 94 hours, then cooling the compressed sample to room temperature, releasing the pressure and measuring the height loss in % based on a compressed height of 1.5 mm.
13. A method for obtaining a polyisocyanurate plastic according to any one of claims 1 to 12, comprising the following steps: i) providing a composition comprising at least one isocyanate-functional polymer containing at least 75% by weight of polyether chains, 1 to 5.2% by weight of urethane groups and 0.7 to 4% by weight of isocyanate groups, relative to the total polymer, - and at least 20% by weight, relative to the total composition, of at least one filler, ii) adding at least one catalyst for trimerization of isocyanate groups, and iii) curing the composition by trimerization of isocyanate groups, preferably at a temperature of 5 to 100°C, more preferably 10 to 90°C, in particular 15 to 80°C.
14. The process according to claim 13, wherein the addition of at least one catalyst in step ii) is carried out by a static or dynamic mixing procedure.
15. Use of the polyisocyanurate plastic according to any one of claims 1 to 12 as a gap filler, in particular as a gap filler with high thermal conductivity, or as a vibration absorber, as a vibration or noise damping material, as a coating, as an adhesive or as a sealing material.
Citation Information
Patent Citations
Polyisocyanate-based adhesive
EP2137224A1
Anhydrously curing polyisocyanate-based adhesives
US20220145149A1
Process for preparing polyisocyanurates and polyurethanes using organic orthoborate catalysts
US3697485A
Process for producing modified organic polyisocyanate
US5102918A